Derek Jarman’s Tempest, William Shakespeare’s Salò - Tomas Elliott (Humanities, 2023)
This article re-evaluates Derek Jarman’s adaptation of William Shakespeare’s The Tempest (1979) based on archival research into the cinematic and historical intertexts that influenced the film. Specifically, it focuses on the impact of Pier Paolo Pasolini on Jarman’s aesthetics, particularly the Italian filmmaker’s last work: Salò, or the 120 Days of Sodom (1975). The article explores how Jarman used Pasolini’s work as a filter through which to frame his adaptation of Shakespeare’s play. In so doing, he produced a decidedly Pasolinian twist on The Tempest, which he explicitly referred to in his notes as “Shakespeare’s Salò.” Bridging the gap between the Renaissance and Jarman’s contemporary moment, Jarman’s film offers a meditation on ideas of captivity and captivation in The Tempest, which extends from the play and film’s literal representations of imprisonment to their exploration of the affective power of performance and spectacle.